Bridging Borders Through Skill Recognition for Migrants in Mexico (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
In this essay, Diego Piazza Almudí offers a preview of how Mexico’s competency certification system—led by CONOCER—can function as a practical bridge for migrants, returnees, and displaced people whose skills are real but often undocumented. Moving from Mexico’s shifting role as a country of origin, transit, destination, and return to the mechanics of competency standards and performance-based assessment, the piece highlights both the promise and the friction of certification as an inclusion tool. Piazza Almudí points to on-the-ground efforts like México Reconoce Tu Experiencia for repatriated citizens, alongside the Pacific Alliance’s emerging work on cross-border recognition and homologation of competency certificates. Rather than presenting certification as a standalone solution, the article surfaces the policy, financing, data, and coordination gaps that shape whether skill recognition translates into decent work and mobility.Keyworks: skills recognition; competency-based certification; CONOCER; migrants; return migration; labor market integration; Pacific Alliance; cross-border recognition; homologation; Mexico